Legal protection of e-consumers in the sale of goods contracts in Malaysia - Roshazlizawati Mohd Nor (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2016)
Consumers justly demand fair treatment and high standards of protection including in online sale of goods. Nevertheless, e-consumers seem to be neglected compared to the attention given to the block and mortar consumers or face-to-face consumers. Even though the e-commerce is a positive phenomenon, the same cannot be said for the legal protection it accords to consumers who resorts to e-commerce transaction. E-commerce sees the need to include consumer protection into the law because there is no genuine equality in the bargaining strength of the contracting parties as propagated in the doctrine of freedom of contract in an e-commerce contract. Therefore, the right of e-consumers to seek redress mainly lie under the Contracts Act 1950, the Consumer Protection Act 1999, the Sale of Goods Act 1957, the Electronic Commerce Act 2006, the Trade Description Act 2011 and the Direct Sale and Anti-Pyramid Scheme Act 1993. This research seeks to construct a comprehensive legal protection basis for e-consumers in Malaysia with a special reference to the sale of goods contract. In doing so, this thesis using the content analysis methodology with critical, jurisprudential, historical and comparative approaches, analyses the comprehensiveness of the existing laws in Malaysia. The study focuses on issues related to pre-contractual issues in e-commerce, the content of e-contract and post contractual issues relates to e-consumers. The pre-contractual issues in e-commerce mainly discusses on the formation of e-contract and misleading information in web advertisements. Meanwhile, the content of e-contract focuses on unfair contract terms used by e-traders and the post contractual issues touches on quality of goods received by e-consumers as well as delivery matters. As such, this research analyses the extent to which the laws of Malaysia provides adequate protection to e-consumers. The discussion includes the analysis on the contract law, the CPA, the ECA, SOGA, the TDA and the DSASA. This study proves that there are hindrances under the contract law and SOGA as well as ECA for the e-consumers to seek remedies. In addition, there exist lacunae and ambiguity in the statutory provisions under CPA which need further amendments. At the end of the research, the researcher outlines several proposals for amendments includes proposed regulatory framework which suits the modus operandi of e-commerce contracting in the interest of all Malaysian e-consumers so that they will get optimum protection, especially in online purchase of goods. Thus, this research can benefit many people such as academicians, e-consumers, legislators, law enforcers and e-traders.